A Comparative Study to Evaluate the Efficacy of Kshara Sutra Ligation and Lord’s Anal Dilatation in Internal Haemorrhoids - Hiteshi; Magotra, Shefali (International Research Journal of Ayurveda & Yoga, 2021)
Background- Sushruta samhita is the pioneer literature of Shalya tantra which not only describes the prevention and management of simple diseases but also the treatment of those which are of dreadful nature, Haemorrhoids (Arshas) being one amongst them. Acharya Sushruta, (su.su.33/4) has placed arshas in a notorious group of diseases known as – ‘MAHA AGADAS’ (Diseases cured with greater difficulties). Aims & Objectives: To study the comparative effect of kshara sutra ligation and lord’s anal dilatation in Arshas (Haemorrhoids) Materials and Methods- The patient fulfilling the clinical criteria for diagnosis of haemorrhoids were randomly selected irrespective of their age, sex, religion, occupation etc. from OPD and IPD section of Department of Shalya tantra, JIAR Hospital and from Arogyadham Ayurveda Clinic. Results: KSL’ scored higher on the parameters, Bleeding 78.57%, Itching 78.125% and Discharge 83.33% as compared to LAD. It can accounted to the fact that KSL reduces or cures proctorrhagia by ligation and phytochemical cauterization of hemorrhoidal mass or vascular cushions and so treats bleeding. Conclusion- It was found that both the treatments i.e. Kshara sutra ligation and Lord’s anal dilatation gave highly significant results individually (intra group) in all the clinical features , but on (inter group) comparison statistically insignificant difference was found between two groups.